Prioritizing candidate agents for the biological control of weeds - Paynter, Quentin (Biological control, 2024)
•Hypothesized predictors of agent impact were investigated with an NZ dataset.•Damaging species in the native range were often damaging in the introduced range.•Agents with a ‘native ecological analogue’ were all unsuccessful.•Success varied with agent guild and taxon.•These factors may assist preliminary agent prioritization. A dataset of weed biocontrol agents released in New Zealand was used to review the importance of several factors that have been hypothesized to be predictors of agent impact. Agents that were observed to be highly damaging (i.e., completely defoliating or killing plants or reducing populations in the field) in the native range were almost invariably highly damaging in the introduced range. In contrast, species that were subject to apparent competition mediated by parasitoids shared with closely related “native analogue” species failed to have an impact on the target weed. Agent guild also helped predict agent impact. In particular, the use of agents that only attack reproductive parts of the plant (e.g., seed and flower-feeders) is unlikely to result in reduced weed populations. A simple framework was developed to score candidate agents based on potential host specificity and predicted impact that could be used to assist the ranking of candidate agents for further investigations at the start of a biocontrol program. Nevertheless, further refinement from incorporating larger datasets is desirable as current parameter estimates are likely to be unreliable.